II Ogólnopolski Kongres Studenckich Kół Naukowych , STER – Strategia – Teoria – Ekonomia – Rozwój’’: The 2nd Polish Congres of Students Science Association “STED – Strategy – Theory – Economics – Development” - Czapski, Grzegorz (Management and Administration Journal, 2021)
x